Pharmacology of absorption and distribution: optimal use of antimalarial drugs in the treatment of severe falciparum malaria in Kenya. - Watkins, WM; Winstanley, P; Marsh, K (1994)
Since 1989, a project at the KEMRI CRC Unit at Kilifi has focused on the design of appropriate and practicable regimens for the treatment of severe falciparum malaria. Initially, there was no data describing the absorption, distribution and elimination of quinine in Kenyan children, who constitute the great majority of patients. Pharmacokinetic studies were conducted to define these variables, which formed the basis for the design of appropriate and practicable treatment regimens. Even with optimal clinical management, the majority is high in cases of severe malaria treated with quinine at Kilifi. Alternative drugs have been studied in a search for a therapeutic regimen that will further reduce mortality.